Infrapatellar fat pad resection or preservation during total knee arthroplasty: a meta-analysis of randomized controlled trials - Changjiao Sun (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background The infrapatellar fat pad (IPFP) or Hoffa’s fat pad is often resected during total knee arthroplasty in order to improve visibility. However, the management of the IPFP during total knee arthroplasty (TKA) is the subject of an ongoing debate that has no clear consensus. The purpose of this review was to appraise if resection of the IPFP affects clinical outcomes. Methods We conducted a meta-analysis to identify relevant randomized controlled trials involving infrapatellar fat pad resection and infrapatellar fat pad preservation during total knee arthroplasty in electronic databases, including Web of Science, Embase, PubMed, Cochrane Controlled Trials Register, Cochrane Library, Highwire, CBM, CNKI, VIP, and Wanfang database, up to March 2020. Results Nine randomized controlled trials, involving 783 TKAs (722 patients), were included in the systematic review. Outcome measures included patellar tendon length (PTL), Insall-Salvati ratio (ISR), rate of anterior knee pain, Knee Society Scores (KSS), and knee range of motion. The meta-analysis identified a trend toward the shortening of the patellar tendon with IPFP resection at 6 months (P = 0.0001) and 1 year (P = 0.001). We found no statistical difference in ISR (P = 0.87), rate of anterior knee pain within 6 months (p = 0.45) and 1 year (p = 0.38), KSS at 1 year (p = 0.77), and knee range of motion within 6 months (p = 0.61) and 1 year (0.46). Conclusion Based on the available level I evidence, we were unable to conclude that one surgical technique of IPFP can definitively be considered superior over the other. More adequately powered and better-designed randomized controlled trial (RCT) studies with long-term follow-up are required to produce evidence-based guidelines regarding IPFP resection.